Children and the Ethics of Creativity Rhythmic Affectensities in Early Childhood Education - Hargraves, Victoria Jane.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book presents a critical reimagining of education and educational research in addressing practices of representation and their relation to epistemology, subjectivity and ontology in the context of early childhood education. Drawing on posthumanist perspectives and the immanent materialism of Deleuze & Guattari to conceive of early childhood education, childhood and indeed, adult life, in new ways, it highlights the powerful role of language in subjectivity and ontology, and introduces affectensity as a concept which can be put to work to undo habitual relations and meanings. It proposes that ethical becomings require the engagement of an expansion and intensification of a body$1 (Bs affect or capacity, and offers readers a provocation for enhancing creative capacity as an ethic. This book is an important contribution to the discussions on methods for living and of ways of thinking commensurate with the orientation of a posthuman turn.s
1 Starting Stratified: The Highchair -- 2 Framing the Creativity of Chaos -- 3 Relations in/between Content and Expression: Moving beyond "This is a cow and a cow says moo" -- 4 Mapping Expression as the Monstrosity of an Earthquake Meets Doing-Curriculum -- 5 Assembling Thought: Experiments in Juxtaposition -- 6 How Creative is Subjectification? Capturing Contingency in the Subject -- 7 Working the In-betweens of Material Expression -- 8 Repetition, Refrain, Creativity -- 9 The Affect of Language: Order-in(g) the Child's World of Bees -- 10 Making Creative Sense of Chaos -- 11 Concluding Rhythms: To Dance.
Keywords: Child development; Education$1 (BPhilosophy.s; Learning; Instruction; Education$1 (BResearch.s; Early Childhood Education; Educational Philosophy; Learning & Instruction; Research Methods in Education